Physics studies at a future linear collider - Tabassam, Hajrah (The University of Edinburgh, 2012)
With the start of the Large Hadron Collider(LHC) at CERN, we will obtain a new understanding of the physics beyond our current limits. New discoveries will be made; but we will require a deeper understanding, which the LHC machine, being a hadron collider, will not be able to elucidate. Instead, we will need an e+e- collider to make precision measurements of the newly discovered phenomena. Electroweak symmetry breaking and the origin of fermion and boson masses are fundamental issues in our understanding of particle physics. The essential piece of electroweak symmetry breaking - the Higgs boson - will probably be discovered at the LHC. If there are one, or more, Higgs boson(s) precise measurements of all properties of the Higgs will be very important. In this thesis I present two measurements of Standard Model Higgs boson properties in the context of the International Linear Collider (ILC) at √s = 500 GeV, using the proposed International Linear Detector (ILD). First a performance study of ILD to measure the branching ratios of the Higgs boson with mH = 120 GeV, where the Higgs boson is produced with a Z-boson via the Higgsstralung process, and the Z decays into e+e- or μ+μ-. It will also be essential to study the Higgs Yukawa coupling. Therefore, in the second part of this thesis, I present a study of e+e- → tt¯H with the aim of making a direct measurement of the the top-Higgs coupling, using the semi-leptonic nal state and mH of 120 GeV. I show that the top-Higgs coupling can be measured with an accuracy of better than 28%.
Keywords: ICL; LHC; Large Hadron Collider; Higgs; branching ratio; Yukawa coupling